A family history of cancer and lung cancer risk in never-smokers: A clinic-based case–control study. Issue 2 (August 2015) - Lin, Huan; Huang, Yi-Sheng; Yan, Hong-hong; Yang, Xue-Ning; Zhong, Wen-Zhao; Ye, Huan-Wen; Yang, Jin-Ji; Zhou, Qing; Wu, Yi-Long
Highlights: Population of both case group and control group were Chinese who never smoked. A history of lung cancer in female relatives was a strong predictor of lung cancer. Risks of familial history in different races may indicate varying susceptibility. Abstract: Objective: Some population-based studies involving lung cancer patients have reported that inherited susceptibility is responsible for the familial aggregation observed in non-smoking lung cancer patients; however, it has been found that the false-negative rates in clinic-ascertained probands are significantly lower than population-ascertained probands. In this clinic-based study, we sought to determine the relationship between a family history of cancer and lung cancer risk in Chinese never-smokers. Methods: In this clinic-based case–control study, all 318 probands and 509 controls were Chinese. The data on demographic characteristics, age, gender, race, lung disease history, living environment, occupational exposure, and smoking history were collected from a structured questionnaire. Multiple conditional logistic regression was used to estimate adjusted odds ratios (aOR) and 95% CIs after adjusting for possible confounders. Results: The risk of lung cancer was increased in individuals with a family history of lung (aOR, 3.21; p  < 0.001) or any other cancer (aOR, 1.79; p  < 0.001). Analyses were carried out using stratified relative gender; first-degree female relatives tended to have a higher risk than first-degree male relatives. Similarly, the aOR for a female developing a malignant tumor was two times greater than controls. Conclusions: Our analysis provides further evidence of the importance of genetic factors underlying lung cancer in patients who are never-smokers, especially in patients with a maternal history of cancer.